The Effect of Water Supply System and the Thickness of Spon Buried on Water to Chinese Cabbage Growth (Brassica juncea) on Aqua Culture Method - Wirosoedarmo, Ruslan; W., J. Bambang Rahadi; Ermayanti, Dita (Jurnal Teknologi Pertanian, 2001)
Aqua culture, as a part of hydroponics system, is cultivation on water as medium. The water has important role not only as nutrition source but also as root growth medium replaced soil function. One of the water supply system on it culture is sub irrigation, pumped regularly and nutrition solute on. Styrofoam perforated in a special distance, according to planting distance use for hold the plants. In every hole of Styrofoam, spon use to help roots absorb nutrition on irrigation water optimally.The research aimed to studying the effect of water supply system, the thickness of spon buried on water to Chinese cabbage growth and their interaction. Randomized block design employed with 3 replicates. Treatments carried out were water supply system (continue and flooding) and the thickness of spon buried on water (1cm, 2 cm and 3 cm).The result showed 1 cm thickness of spon buried on water significantly effect to Chinese cabbage height i.e. 8,795 cm, it is the highest result. The lowest result is 7,82 cm for 3 cm thickness of spon buried on water treatment. There is no interaction of two treatments to the amount of leaves, width of leaves and length of roots.Keywords: Chinese cabbage growth, water supply system, aqua cultureÂ